KEARIFAN LOKAL DALAM PRAKTIK SPIRITUAL DAN ARSITEKTUR: STUDI KOMPARATIF CANDI BOROBUDUR (INDONESIA) DAN KUIL KIYOMIZUDERA (JEPANG) - Rahadiyan Duwi Nugroho; Titien Wahyu Andarwati; Cahyaningsih Pujimahanani; Cicilia Tantri Suryawati; Putut Handoko (SABANA: Jurnal Sosiologi, Antropologi, dan Budaya Nusantara, 2025)
Borobudur Temple in Indonesia and Kiyomizudera Temple in Japan are Buddhist places of worship reflecting local wisdom in spiritual practices and architectural structures. This study aims to analyze the values of local wisdom in the spiritual and architectural aspects of both structures, which contribute to a system of meaning, social practices, and community identity. The benefit is to enrich knowledge about the local wisdom embodied in these two historical buildings, which also function as Buddhist places of worship. The method employed is a comparative study using a descriptive qualitative approach through literature review. Findings reveal that Borobudur Temple, influenced by Mahayana Buddhism, reflects local wisdom through communal cooperation (gotong royong), harmony with nature, and spiritual symbolism in its reliefs and tiered structure (kamadhatu, rupadhatu, arupadhatu) representing the path to enlightenment. Meanwhile, Kiyomizudera Temple, influenced by Tendai Buddhism, expresses local wisdom through spiritual activities such as pilgrimage, ritual use of Otowa Waterfall, and the application of traditional, nail-free wooden construction techniques that are earthquake-resistant. The temple is also designed to blend with its natural surroundings and foster inner peace. In conclusion, both structures represent a fusion of spiritual values, traditional architecture, and cultural preservation, reflecting the profound understanding of past societies regarding the interconnection between humanity, nature, and spirituality